Mutations that affect control of the methylesterase activity of CheB, a component of the chemotaxis adaptation system in Escherichia coli. - Stewart, R C (1990)
Sensory adaptation by the chemotaxis system of Escherichia coli requires adjustments of the extent of methyl esterification of the chemotaxis receptor proteins. One mechanism utilized by E. coli to make such adjustments is to control the activity of CheB, the enzyme responsible for removing receptor methyl ester groups. Previous work has established the existence of a multicomponent signal transduction pathway that enables the chemotaxis receptor proteins to control the methylesterase activity in response to chemotactic stimuli. We isolated and characterized CheB mutants that do not respond normally to this control mechanism. In intact cells these CheB variants could not be activated in response to negative chemotaxis stimuli. Further characterization indicated that these CheB variants could not be phosphorylated by the chemotaxis protein kinase CheA. Disruption of the mechanism responsible for regulating methylesterase activity was also observed in cells carrying chromosomal deletions of either cheA or cheW as well as in cells expressing mutant versions of CheA that lacked kinase activity. These results provide further support for recent proposals that activation of the methylesterase activity of CheB involves phosphorylation of CheB by CheA. Furthermore, our findings suggest that CheW plays an essential role in enabling the chemotaxis receptor proteins to control the methylesterase activity, possibly by controlling the CheA-CheB phosphotransfer reaction.